Weight variation over time and its relevance among multidrug-resistant tuberculosis patients - Chung Delgado, Kocfa (2014)
Objectives: We aimed to assess the variation in patient body weight over time according to the treatment outcome among multidrug-resistant tuberculosis (MDR-TB) cases. Methods: This was a retrospective cohort study. The data of patients commencing MDR-TB therapy were analyzed. Data were collected from different public TB treatment facilities located in peri-urban areas to the south of Lima, Peru. The outcome was patient body weight (kilograms) from treatment commencement, measured monthly. A random effects model was fitted using robust standard errors to calculate 95% confidence intervals. Results: Of a total of 1242 TB cases, 243 (19.6%) were MDR-TB. Only 201 cases were included in the analysis; 127 (63.2%) were males and the mean patient age was 33.6 (standard deviation 16.2) years. Weight changes over time among the patients who were cured differed from changes in those who died during therapy (p < 0.001). Weight curve divergence was important at the end of the third, fourth, and fifth treatment months: on average, the weight difference was 2.18 kg (p < 0.001), 3.27 kg (p = 0.007), and 3.58 kg (p = 0.03), respectively, when cured patients were compared to those who died. Conclusions: Our results show that weight variation during treatment can be a useful surrogate for the treatment outcome, specifically death during therapy. MDR-TB patients with weight loss should be followed more closely, as they are at greater risk of death.